2018
DOI: 10.1002/ijfe.1612
|View full text |Cite
|
Sign up to set email alerts
|

Do credit ratings affect spread and return? A study of structured finance products

Abstract: Although the previous studies investigating the relationship between credit ratings and spread or return in the financial market are normally restricted to noncausal measures, this paper uses structural equation modelling to test the possibility of causal links from ratings to spread and return in the context of structured finance products. Our analyses are split into 2 stages: First, we search for causality between ratings and spread at the issuance stage (primary market) based on a sample comprising all tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…BCRs are arguably more efficient in reflecting overall performance since banks are inherently opaque, but are exposed to a multiplicity of risks, and hence, stakeholders tend to rely on independent ratings provided by rating agencies as a way of assessing their financial viability (Beisland et al, 2014; Kusi & Opoku‐Mensah, 2018; Moreira & Zhao, 2018). One reason is that the rules that independent credit rating agencies apply to measure bank ratings do not rely on banks' conventional performance metrics only, but also on other characteristics.…”
Section: Bcrs Risk Disclosure and Governance Reforms In Mena Banksmentioning
confidence: 99%
“…BCRs are arguably more efficient in reflecting overall performance since banks are inherently opaque, but are exposed to a multiplicity of risks, and hence, stakeholders tend to rely on independent ratings provided by rating agencies as a way of assessing their financial viability (Beisland et al, 2014; Kusi & Opoku‐Mensah, 2018; Moreira & Zhao, 2018). One reason is that the rules that independent credit rating agencies apply to measure bank ratings do not rely on banks' conventional performance metrics only, but also on other characteristics.…”
Section: Bcrs Risk Disclosure and Governance Reforms In Mena Banksmentioning
confidence: 99%
“…Following a growing body of literature (e.g., Moreira & Zhao, 2018; Morgan & Winship, 2007; Mulaik, 2009; Pearl, 2009), we use structural equation modelling (SEM) to test and evaluate multivariate causal relationships between the variables of interest. This covariance‐based approach is a combination of factor analysis and multiple regression analysis, and it is used to analyse the structural relationship between measured variables and latent constructs.…”
Section: Methodsmentioning
confidence: 99%
“…This covariance-based approach is a combination of factor analysis and multiple regression analysis, and it is used to analyse the structural relationship between measured variables and latent constructs. Although this approach is often applied in issues with latent variables, it can also be used to study observed variables alone (Moreira & Zhao, 2018).…”
Section: Modelling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign scholars have explored the pricing factors of structured products. In terms of credit rating, (Moreira and Zhao 2018) pointed out that there is a big connection between ABS ratings and their yield spread at issuance in the US market, Credit ratings may affect investors' investment decisions during the issuance stage. Fabozzi and Vink (2012) explored the influencing factors of asset-backed securitization in the European market, indicating that investors will consider other credit factors such as credit enhancement and underlying assets in addition to credit ratings.…”
Section: Issuance Pricing and Impact Factors Of Green Asset-backed Securitiesmentioning
confidence: 99%